Anticancer activity of monastrol, hybrids and derivatives: A comprehensive bibliometric analysis of recent research - Wilson Cardona Galeano, Howard Ramírez-Malule, David Gómez-Rios (Journal of Applied Pharmaceutical Science, 2024)
Due to the high incidence and mortality rates of cancer, as well as the undesirable side effects associated with conventional chemotherapy treatments, there is a growing focus on investigating novel chemopreventive pharmaceutical agents. Dihydropyrimidinone and its derivative, monastrol, have shown promising anticancer activity by locking bipolar mitotic spindle by targeting the mitotic kinesin-5 motor protein Eg5. Synthesis of monastrol derivatives and hybrids, as well as the assessment of their potential antiproliferative effects on cancer cell lines, is a current field of research with a high scientific output. This paper presents a comprehensive bibliometric analysis of published research on monastrol and their derivatives and hybrids, highlighting the growth of published studies, the main areas of knowledge, and the leading countries in terms of publication, among others. In addition, the co-occurrence of authors’ keywords networks and bibliometric networks are presented, providing an overview of the areas of focus in monastrol research. The main areas of knowledge in the field were (i) biochemistry, genetics, and molecular biology, (ii) Chemistry and pharmacology, and (iii) toxicology and pharmaceutics. Furthermore, the United States, China, Brazil, the United Kingdom, and Germany were the most productive countries in terms of the number of published studies. Finally, the results suggest that research on monastrol derivatives and hybrids has increased significantly, with molecular docking and cytotoxicity studies being the most prominent areas of focus.
Keywords: Monastrol, hybrids, anticancer activity, bibliometric analysis